How does agricultural insurance induce farmers to adopt a green lifestyle? - Hou, Dainan; Wang, Xin (Frontiers in Psychology, 2023)
This study is dedicated to exploring and establishing a theoretical framework for the impact of agricultural insurance on farmers’ green lifestyles. By thoroughly analyzing existing literature, this paper reveals the dual pathways through which agricultural insurance influences farmers’ behavior: one affects production activities, and the other affects lifestyle choices. Drawing on the Stimulus-Organism-Response (SOR) theory, the study elaborates in detail the incentive mechanisms of agricultural insurance, farmers’ cognition of green practices, and how these elements work together to guide a transformation in farmer behavior. This process systematically demonstrates the theoretical logic and pathways through which agricultural insurance promotes the transition to green lifestyles among farmers. Additionally, the study provides a preliminary description of the questionnaire design and its role in supplying foundational data for empirical analysis. The paper posits that agricultural insurance harbors an intrinsic mechanism to induce farmers toward greener lifestyles. We anticipate that this research will bring new perspectives to the field of agricultural insurance and contribute new dimensions to the theoretical framework of behavioral insurance.